2023
DOI: 10.3389/fnut.2023.1079250
|View full text |Cite
|
Sign up to set email alerts
|

Health effects of the time-restricted eating in adults with obesity: A systematic review and meta-analysis

Abstract: BackgroundThe number of people suffering from overweight or obesity has been steadily increasing in recent years. As a new form of diet, the efficacy of time-restricted eating (TRE) remains debatable.ObjectiveThis meta-analysis quantified the effect of TRE on weight change and other physical parameters in obese and overweight adults.MethodsWe did a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing the TRE interventions on weight loss and other metabolic parameters by searchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…However, the intervention effect of TRE in health improvement was greatest in the e-TRE subgroup with considerable energy deficit. The relatively modest magnitude has been demonstrated in some previous meta-analysis, some attributed this to the short intervention duration 45 while other did not find the association between health improvement and duration. 34 Thus, more long-term TRE studies are needed to get a more solid conclusion, both in people with overweight or obesity status and patients with metabolic symptoms.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…However, the intervention effect of TRE in health improvement was greatest in the e-TRE subgroup with considerable energy deficit. The relatively modest magnitude has been demonstrated in some previous meta-analysis, some attributed this to the short intervention duration 45 while other did not find the association between health improvement and duration. 34 Thus, more long-term TRE studies are needed to get a more solid conclusion, both in people with overweight or obesity status and patients with metabolic symptoms.…”
Section: Discussionmentioning
confidence: 69%
“…This modest reduction was in line with previous meta-analysis so we further do meta-regression to explore the mechanism of weight loss in TRE strategies. 34 , 35 , 36 , 45 Meta-regression showed that weight loss was significantly related to energy consumption ( Z = 5.23, p < 0.001) and the eating window ( Z = 2.26, p = 0.024) but was not correlated with the intervention duration ( Z = 0.36, p = 0.72). This demonstrated an increased capacity for TRE to cause weight loss by a greater calorie deficit and shorter eating window within a safe range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRE is a form of intermittent fasting involving a period of fasting and eating within each 24‐h period for example, 16:8 (16 h fasting and 8 h eating) 20 . Substantial evidence exists supporting the effectiveness of TRE in achieving substantial weight loss, cardiometabolic health, and mental health 21,22 . Despite this, there remains limited evidence evaluating a digital TRE program in patients living with overweight and obesity, particularly in the real world and in a workplace setting.…”
Section: Introductionmentioning
confidence: 99%
“…The 5:2 diet involves limiting energy intake to 500 calories in women and 600 calories in men, for two non-consecutive days per week, with unrestricted eating for the rest of the week [13]. TRE is slightly different, as it involves following the same routine every day, where you eat within a certain window of hours and fast in the remaining hours [14], for example, the 16:8 diet, where eating is only allowed within an 8 h window each day [15].…”
Section: Introductionmentioning
confidence: 99%